Bimbingan Penggunaan Google Form Dalam Pembuatan Soal Bagi Guru Sekolah Dasar - Septikasari, Resti; Dewi, Tri Ratna; Dewi, Sri Enggar Kencana; Pertiwi, Ratih Purnama (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2020)
Based on the results of the study, it is known that the use of Google Forms as a tool for making questions in learning is more effective and efficient than assignments via WhatsApp. Teachers can use the Google Form for the next lesson. Judging from the results of the research, Teacher A gets a score of 60, 70, 100, Teacher B gets a score of 80, 100, 100, teacher C gets a score of 50, 60, 90, teacher D gets a score of 80, 80, 100 and teacher E gets a score of 75, 90 , 100. From the five teachers, there was an improvement even though there was one teacher who initially did not understand the Google Form but was able to get a fairly large score in the end. The use of Google Forms used by teachers as student assignment activity sheets is part of providing meaningful learning experiences for students who have indirectly introduced digital technology to them.